Effects of Smoking on Systemic Blood Pressure, Serum Cholesterol and Serum Bilirubin in Medical Students (Medical Forum Monthly, 2024)
Objective: To determine the effects of smoking on systemic blood pressure, serum cholesterol and serum bilirubin in medical students.Study Design: Case control studyPlace & Duration: This study was conducted at the Liaquat University of Medical and Health Sciences Hospital from June 2014 to November 2014.Materials and Methods: A sample of 100 medical students was divided into 50 smokers and 50 non-smokers. Age, weight, smoking duration, blood pressure, serum cholesterol and serum bilirubin were collected in a pre structured proforma. Data was analyzed by statistical package SPSS 22.0.Results: Duration, cigarettes smoked and pack year of cigarette smoked were noted as 3.85 ± 3.96 years, 10.25 ± 3.57 and 1.7±0.56 respectively (p=0.0001). Mean systolic and diastolic BP in smokers and non-smokers noted as 143.9±12.67 and 135.1±15.24 (p=0.002), 75.6±9.72 and 67.9±6.06 mmHg (0.0001) respectively. Similarly serum bilirubin and cholesterol were noted as 0.99±0.27 and 1.13±0.20 (p=0.005), 156.5±18.6 and 119.3±22.70 mg/dl (p=0.0001) respectively.Conclusion: The present study reports high systemic blood pressure and serum cholesterol and low serum bilirubin in the smokers. Preventive strategies must be implemented to quit the smoking by youngsters.